Penerapan Well-Being Therapy Untuk Meningkatkan Psychological Well-Being pada Penderita Kanker Payudara - Maqhfirah DR (Universitas Negeri Medan, 2015)
Having breast cancer have a huge impact on quality of life of survivors. One of it is decreased psychological well-being. Psychological well-being is a description of the psychological health of individuals based on the fulfillment of the criteria that individual positive psychological functioning, encompassing self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life and personal growth. Well-being therapy can apply to increase the level of psychological well-being in breast cancer survivors. Participants this study are two women with post-mastectomy breast cancer, metastases experienced last year, and is undergoing medical treatment such as chemotherapy. Well-being therapy conducted within a month, in five sessions. Results indicate that application of well-being therapy has changed their psychological well-being level to the better. They were more accepting with their health condition and have better relationships with the significant people. This is clout by good motivation, support from their significant people during the therapy of process and using of religious aspects as one way in eudomanic approach to well-being therapy. In addition, the good rapport between researcher and participants is important to supported therapeutic effect.